Prevalence and factors associated with erectile dysfunction in male patients with human immunodeficiency virus in a teaching hospital in west Malaysia - Enoma, Aghahowa; Ching, Siew Mooi; Hoo, Fan Kee; Syed Omar, Sharifah Faridah (Malaysian Medical Association, 2017)
Introduction: Erectile dysfunction (ED) has been associated with the treatment of human immunodeficiency virus (HIV) and chronic diseases. Sexual dysfunction data of male patients infected with HIV are still scarce in Malaysia, and ED appears to be under-reported. Therefore, this study aims to determine the prevalence and predictors of ED among male HIV patients at the University Malaya Medical Centre. Methods: A cross sectional study was conducted among male HIV patients on antiretroviral therapy (ART) attending the outpatient clinic of a teaching hospital in Malaysia. A systematic random sampling method was employed in the selection of respondents. Participants were interviewed using a structured questionnaire with a 15-item international index of erectile function (IIEF-15). An appropriate statistical analysis was used to determine the associate and potential risk factors. Results: A total of 220 males participated in this study with a mean age of 37.9±9.9; prevalence of ED among HIV patients was 82.3 % (n=180). The severity of ED was further categorized into: severe (24.1%), moderate (19.1%), mild to moderate (20.9%), and mild (18.3%). In a multivariate logistic regression analysis, patients with a lower educational background were more likely to be associated with ED (odds ratio [OR] 2.62, 95% confidence interval [CI] 1.02-6.72; p-value 0.046). Conclusion: This study reports that ED was prevalent among adult HIV males who are on an ART regimen. Those with a lower educational background are more likely to have ED. Hence, in managing patients with HIV, physicians should seek to identify those patients at risk of developing ED for further intervention.